2012
DOI: 10.1055/s-0032-1325324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between CT and CEUS in the Diagnosis of Pancreatic Adenocarcinoma

Abstract: US/CEUS sensitivity in diagnosing pancreatic ductal adenocarcinoma is adequate and does not statistically differ from that of MDCT. US/CEUS sensitivity seems to be higher for small and medium lesions, while MDCT sensitivity is higher for large lesions. By combining both the imaging methods a higher accuracy in diagnosing pancreatic ductal adenocarcinoma can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 2 publications
1
29
0
1
Order By: Relevance
“…The diagnostic accuracy of CEUS in hypoenhancing pancreatic lesions was 89.1% in our study, which was consistent with the results of studies by Yan et al and D'Onofrio et al [19,20]. In particular, in PAMUS [3] ductal adenocarcinomas were correctly identified with an accuracy of 87.8% based on the hypoenhancing aspect at CEUS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The diagnostic accuracy of CEUS in hypoenhancing pancreatic lesions was 89.1% in our study, which was consistent with the results of studies by Yan et al and D'Onofrio et al [19,20]. In particular, in PAMUS [3] ductal adenocarcinomas were correctly identified with an accuracy of 87.8% based on the hypoenhancing aspect at CEUS.…”
Section: Discussionsupporting
confidence: 92%
“…The main advantage of CEUS, as compared to other imaging techniques, is the ability to obtain a dynamic study, a real-time observation of blood perfusion of the lesion. With high spatial and temporal resolution for a relatively long time after microbubbles bolus, CEUS tends to gain lot of confidence in the characterization of pancreatic lesions [2,19]. Due to the fixed time of scanning, CE-CT/ MRI cannot capture a transient enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively new for the pancreatic evaluation, CEUS represents a safe and feasible technique to immediately better characterize and stage the disease during single US examination [33]. Our review found few studies investigating the vascular pattern of pathologically proven pancreatic tumors and enrolling more than 100 patients [1, 11,12,15,20,26,28]. However, during the last ten years we observed a progressive increase in published papers regarding CEUS of the pancreas.…”
Section: Methodological Qualitymentioning
confidence: 96%
“…The pooled estimate of DOR was 57.63 (95 % CI 33.62 -98.78). CEUS has been shown to be an accurate imaging method in the evaluation of pancreatic lesion vascularity and in the differentiation between solid and cystic lesions, thus influencing the choice of further examinations, as well as being useful in obtaining an immediate and faster diagnosis [3,4,12]. Regarding pancreatic adenocarcinoma a rapid diagnosis is very important.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…As a consequence, CEUS shows vascularization exactly in real time, allowing a dynamic study of the enhancement pattern, including wash-in and washout. [18][19][20][21][22][23][24] Pancreatic enhancement begins almost at the same time as aortic enhancement due to an almost exclusively glandular arterial supply, giving an early postcontrast phase, called arterial/pancreatic (from 10 to 30 seconds). Then there is the venous phase (from 30 to ≈120 seconds) and the late phase (≈120 seconds).…”
Section: B-mode and Tissue Harmonic Imagingmentioning
confidence: 99%